Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

YES Program Book - Youth Employment Services (YES) (2020)

Small Business Resource Guide - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, we have compiled a resource guide for small businesses to help you navigate these challenging times.

Program Book - Youth Employment Services (YES) (2020)

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Annual Report 2019-2020 : Broadening Access for Better Futures - Youth Employment Services (YES) (2020)

Who We Are - Youth Employment Services (YES) (2020)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Closing the 12k Gap : Improving Employment for Quebec's English Community - Conference Report - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Youth Employment Services (YES) is pleased to have secured funding from the Secretariat for relations with English-peaking Quebecers (SRQEA) to build a stronger network of English service organizationsworking in employability. The Provincial Employment Roundtable (PERT) project aims to address three important employment issues facing English speakers in Quebec.

Combler l'écart de 12 000 Emplois : améliorer l'emploi pour la communauté d'expression anglaise du Québec - rapport de conférence - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Services d’emploi pour les jeunes (YES) est heureux d’avoir obtenu du ﬁnancement du Secrétariat des relations avec les Québécois anglophones (SRQEA) aﬁn de bâtir un réseau plus solide d’organismes de services en anglais qui travaillent dans le domaine de l’emploi. Le projet de la Table ronde provinciale sur l’emploi (PERT) a pour objectif d’aborder trois questions importantes en matière d’emploi auxquelles doivent faire face les anglophones au Québec.

Transferable Skills & Your 2020 Job Search - Voice of English-speaking Quebec (VEQ); Youth Employment Services (YES) (2020)